Progressive Damage Mechanism of Rocks Subjected to Cyclic Loading - Geranmayeh Vaneghi, Rashid (Curtin University, 2020)
This thesis investigates the effect of cyclic loading conditions on the strength and deformation behaviour of rock materials under uniaxial compression. Two microstructurally and mineralogically different rocks are considered in this experimental investigation. Variations in loading stress level, stress amplitude and frequency are considered to derive novel conclusions on the damage mechanism and fatigue strength. The investigation revealed the greater susceptibility of hard rocks to cyclic loading compared to soft rocks.